Disparities in colorectal cancer between Northern and SouthernSweden – a report from the new RISK North database. (2nd December 2018) - Sjöström, Olof; Silander, Gustav; Syk, Ingvar; Henriksson, Roger; Melin, Beatrice; Hellquist, Barbro N.
Abstract: Background: Geographic cancer health disparities have been reported in Sweden. The disparities are not fully understood, but may be attributed to differences in exposure to risk factors as well as differences in health care, socioeconomics and demography. The aim of this study was to describe the new nationwide population based RISK North database and its potential by analysing health disparities in colorectal cancer between Northern and Southern Sweden. Methods: Cancer-specific data from the National Cancer Quality Registers for colorectal, gastric and oesophageal cancer and brain tumours were linked to several nationwide registers hereby creating a new database – RISK North. To exemplify the potential of RISK North, we analyzed differences in colorectal cancer incidence, mortality and survival in relation to gender, age, cohabitation and education between Northern and Southern Sweden 2007–2013. Results: In colon cancer, the age-adjusted incidence per 100.000 was lower in Northern than Southern Sweden, 35.9 in the North vs. 41.1 in the South ( p < .01); mortality rates were 11.0 vs. 12.2 ( p < .01). For rectal cancer, incidence rates were 17.6 vs. 19.7 ( p < .01) and mortality rates 5.33 vs. 5.89 ( p = .07), respectively. The largest difference in incidence was demonstrated for colon cancer among individuals >79 years old (190. vs. 237, i.e., ∼20%). Survival in colon cancer was higher in Southern Sweden, HR 0.92 (0.87–0.98) adjusted for age, gender, co-habiting, education and m-stage at diagnosis. No difference in survival was seen for rectal cancer. Conclusions: The new RISK North database enabled analysis of cancer disparities between Northern and Southern Sweden. The incidence of colorectal cancer were lower in the North of Sweden whereas colon cancer survival was higher in the South. These differences can be further analysed utilising the RISK North database.